Spinal cord stimulation in chronic pain treatment – first experiences in Bosnia and Herzegovina - Tatjana Bućma; Ostoja Savić; Tatjana Boškić; Lena Arambašić Topić; Igor Sladojević; Snježana Novaković Bursać (Medicinski glasnik, 2022)
Aim: To describe results of spinal cord stimulation technique when the conventional multidisciplinary treatment of neuropathic or mixed pain failed. Methods: The research was conducted at the Institute for Physical Medicine and Rehabilitation “Dr. Miroslav Zotović”, Banjaluka. Ten patients, who had chronic pain resistant to other therapeutic options and a failed back surgery, were sent for an evaluation. Each patient underwent a 4-week evaluation by a team of medical specialists, phychologist and social workers. Additional diagnostic methods (MRI of the lumbosacral spine, electromyoneurography of lower extermities, congnitive assessment tests) were also performed to establish a proper indication for implantation of the system for spinal cord stimulation. Leads of a system for spinal cord stimulation were implanted percutaneously or surgically at the epidural space. Functional outcome measures (visual analogue scale, Oswestry index, anxiety and depression scales) were taken before the implantation of the system and on several followups. Results: Four patients did not meet critea for the inclusion in the study (two were not ready, two showed psychopathological symptoms). One patient had a percutaneous lead implant, but it was removed after six months due to paresthesia. The remaining five had surgicaly implanted epidural leads and showed significant improvement in pain control, Oswestry index had lower values, and all except one patient had improvement registered by anxiety and depression scales. Conclusion: Short-term and long-term follow up showed a long lasting pain reduction and improvement of functionality in all patients.
Keywords: electric stimulation therapy; failed back surgery syndrome; treatment outcome